Bendable transparent conductive meshes based on multi-layer inkjet-printed silver patterns. (4th February 2016) - Yu, Po-Chin; Hong, Chien-Chong; Liou, Tong-Miin
Abstract: Many consumer electronics manufacturers have used transparent conductive films in solar cells, LED devices, and touch panels as a medium for simultaneous electric charge transportation and light transmission. The conductivity and transmittance of transparent conductive films greatly affect the efficiency of these optoelectronic devices. This study presents a transparent and conductive mesh based on inkjet-printed silver and conductive polymer. Also, we propose a mathematical model for calculating the optimized mesh pattern. The proposed model precisely calculates an optimized line-width-to-line-spacing ratio. Furthermore, the results of our experiment verify the relationship between the line-width-to-line-spacing ratio and figure of merit. Compared with the equations of past studies, the equation proposed in this study is valid for a broader range of line-width-to-line-spacing ratios. In addition, the theoretical results of our study correlate more strongly with the experimental data of this study than with that of previous studies. To achieve the highest figure of merit, the values of the filling factor and the line-width-to-line-spacing ratio should be 0.05 and 19, respectively. Finally, we reduced the sheet resistance of the inkjet-printed mesh by 97.9% by applying multilayer printing. However, we were able to reduce only the optical transmittance of the mesh by 3.0%. The developed inkjet-printed silver meshes can survive more than 3500 bending tests simultaneous with application of 300 mA current.